The Reasons for L1 Use by English Teaching Turkish Teachers in Turkish Schools - TOMAK, BURAK (ANI YAYINCILIK, 2021)
Purpose: Some argue that L1 should be strictly prohibited in language classrooms, whereas some studies claim that the integration of L1 (first language) in L2 (second language) teaching will facilitate learning. Thus, in this sense, this study was conducted in eight different Turkish schools to find out how much L1 was used in English language classes and why it was used in those cases. Research Methods: With the help of an observation protocol used to record the lessons' relevant moments, eight different teachers working in eight different schools were observed for at least one lesson hour to figure out whether they turned to L1 during their teaching and why they did it. In addition to on-site observations, open-ended questionnaires were applied to students in two different schools and an interview was conducted with a teacher in one of these schools for this study's purpose. Findings: It was found that most of the teachers were trying to use as much L2 as possible though there were times they used their native tongue (which is Turkish in this context) for several reasons, including humour, explanation of a grammatical rule, pronunciation, to encourage learners to learn English, clarification, classroom management, and error correction. Implications for Research and Practice: This case study can also be conducted in different contexts to determine the situation and whether the same reasons apply for different contexts. (C) 2021 Ani Publishing Ltd. All rights reserved
Keywords: English language classrooms; Turkish language use; ELT; LANGUAGE; CLASSROOM; HUMOR